Sistema de monitoramento de docas com recursos da indústria 4.0 estudo de caso com uma interface em realidade aumentada e IOT em uma fábrica de televisores. - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The constant technological advancement contributes so that various sectors of the industry can change and update themselves to meet the new market demands. Industry 4.0 has been bringing new paradigms that define how the industry should behave in this new scenario. Augmented reality (AR) technology, as one of the pillars of the 4.0 concept, enables new ways to adopt information technology and promote this updating. Despite its great potential, there is still a lack of specific studies on the construction of simple and effective AR interfaces, integrating fluidly into routines. Considering this context, the objective of this dissertation is to elaborate an AR interface prototype to simplify the management of JIT (Just in Time) docks and, by means of a case study, verify its applicability in a television set factory in the Industrial Pole of Manaus. To conduct this research, the Double Diamond method was applied to understand the current state of studies on UX and UI and to promote innovation in the construction of an AR interface directed for use in industry. The results contemplate the construction of an IoT System and a mobile application with an appropriate Interface for use with AR.
Dock monitoring system with industry 4.0 features case study with an augmented reality interface and IOT in a tv factory
Keywords: CIENCIAS EXATAS E DA TERRA; Design de Interface; Realidade Aumentada; Indústria 4.0